Development of the STEM-Pedagogical Content Knowledge Scale for Pre-service Teachers: Validity and Reliability Study - Behiye Akçay; Filiz Avcı (Universitas Pendidikan Indonesia, 2022)
This study aims to develop a valid and reliable scale to determine the STEM-Pedagogical Content Knowledge (STEM-PCK) levels of pre-service teachers. This study was conducted in the 2018-2019 academic year with 322 pre-service teachers in Turkey. In the study, one of the mixed method typologies, Exploratory Sequential Design was applied. The scale was submitted for evaluation by four experts to determine the content and face validity. Exploratory Factor Analysis (EFA) and Confirmatory Factor Analysis (CFA) was performed to determine the construct validity of the scale. As a result of EFA, the scale had five factors including STEM Pedagogical Knowledge, Pedagogical Knowledge, Engineering Pedagogical Knowledge, Mathematics Pedagogical Knowledge and Science Pedagogical Knowledge.As a result of CFAχ ² / df = 2.7085, RMSEA = .073, RMR = 0.0420, SRMR = .0667, NFI = .940, NNFI = .960, CFI = .961, IFI = .962, RFI = .938 values were reached and the factor structure determined to be suitable.To determine the reliability of the scale, internal consistency and test-retest reliability analyzes were made. Internal consistency reliability value of the scale was found as .977. The final form of the STEM-PCK scale is a 5-point Likert type that includes 57 items and 5 factors.